Review Virus Chikungunya - Grenshannya Anasthasya Pua; Fatimawali Fatimawali; Irma Antasionasti (UNIVERSITAS SAM RATULANGI, 2022)
Chikungunya is a virus belonging to the family Togaviridae and genus Alphavirus which was first isolated in Tanzania in 1953. This virus transmission by mosquito vectors, namely Aedes aygepti and Aedes albopictus. Indonesia itself is included as the country that has the largest burden of Chikungunya in Southeast Asia. Symptoms caused by this viral infection are severe enough to cause temporary paralysis and prolonged joint pain. Chikungunya virus drugs and vaccines are not yet officially available and are licensed only in the form of symptomatic treatment that can be given to reduce symptoms. Research and development of Chikungunya virus treatment and vaccines are currently being developed to control the spread of the Chikungunya virus.Â